2020
DOI: 10.22190/fupes191119055s
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Somatotype of Top Young Race Walkers by Means of the Heath-Carter Method

Abstract: The aim of this study was to analyze the somatotypes of top young race walkers in Europe. For the analysis of their somatotype, the Heath-Carter method was used.  By applying digital anthropometry and computer programs, the somatotypes of 44 participants aged 15 to 17, sports walkers of both genders (21 boys and 23 girls), were determined. Based on the analysis, extensive data were obtained on the somatotype of top young race walkers, where a large number of groups emerged. Among the boys, there are three grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
1
5
0
1
Order By: Relevance
“…Also Zar A, et al [27] observed that there is a significant correlation with the level of body activity and Blood temperament and that is in accordance with founding about mesomorph components. It is observed that most of the trained mail martial art players mostly have mesomorph somatotypes [5] and this finding might partially explained that mesomorphy component provides a comparative advantage to these players which is indeed similar to those of Mahdizadeh R [29] and our findings. Gualdi-Russo E, and Graziani I [36] in 1993 determined the somatotypes of 717 male young sport participants and found that the mesomorphy component was greater than the other two components [36].…”
Section: Statistical Analysis Endomorphy Mesomorphy Ectomorphysupporting
confidence: 87%
See 1 more Smart Citation
“…Also Zar A, et al [27] observed that there is a significant correlation with the level of body activity and Blood temperament and that is in accordance with founding about mesomorph components. It is observed that most of the trained mail martial art players mostly have mesomorph somatotypes [5] and this finding might partially explained that mesomorphy component provides a comparative advantage to these players which is indeed similar to those of Mahdizadeh R [29] and our findings. Gualdi-Russo E, and Graziani I [36] in 1993 determined the somatotypes of 717 male young sport participants and found that the mesomorphy component was greater than the other two components [36].…”
Section: Statistical Analysis Endomorphy Mesomorphy Ectomorphysupporting
confidence: 87%
“…Some of them believe that differences in body types can clearly determine athlete's success or failure in the most type of competitions. According to some authors, in order to create athlete's profile, It's very essential in all branches of sports and each sports needs specific body type from athletes [2][3][4][5]. Sheldon WH, et al 1940 [6], one of the older pioneer of somatotype's researchers, reconstructed the term somatotypes and they build their own typology starting from the three primary germ layers.…”
Section: Introductionmentioning
confidence: 99%
“…Mahdizadeh R in 2013 argued that individual temperament is a determinative factor of human motivation to have body activity [12] and damvi mizaj persons have a physical structure that is essential for hard physical activity [13] . Zar A, et al observed that there is a significant correlation with the level of body activity and damvi mizaj is in accordance with mesomorph somatotype components [16] which was mostly observed in trained martial art players in another study [17] . This suggests that results of our study that Damvi mizaj has highest mean physical fitness index is in concordance with these studies.…”
Section: Discussionmentioning
confidence: 79%
“…Lokal Nasional Internasional secara keseluruhan tipe tubuh yang dominan dimiliki oleh atlet seni gerak tarung derajat cenderung memiliki tipe tubuh endomorph mesomorph sebesar 67% . Hasil penelitian ini sama pada penelitian sebelumnya yang mengatakan bahwa tipe tubuh endomorphmesomorph terdapat pada atlet beladiri sambo pria (Trivic et al 2020), atlet tarung derajat kategori petarung (Suryadi et al 2022), pemain pedel elit (De La Fuente et al 2019;Sánchez-Muñoz et al 2020;Stanković et al 2020), dan dominan pada atlet tenis meja (Penggalih et al 2018), sebuah artikel mengatakan kuda-kuda dan kestabilan power lebih memiliki keuntungan pada tipe tubuh endomorph mesomorph (Khairunnisa Balqis et al…”
Section: P R E S T a S I S O M A T O T Y P Eunclassified